Self-efficacy, attitudes, knowledge, and school support as predictors of STEM teachers' pedagogical approach to sustainable development - Maslamany, Kavitha; V Sathasivam, Renuka; Chua, Kah Heng (LUMAT: International Journal on Math, Science and Technology Education, 2025)
This study aims to assess the influence of STEM teachers' ESD teaching self-efficacy, attitudes towards Sustainable Development (SD), knowledge about SD, and school support on their adoption of SD-oriented pedagogical approaches in alignment with the Sustainable Development Goals (SDGs). A quantitative research design was employed, involving surveys administered to 896 primary school STEM teachers across Malaysia, selected through stratified random sampling. The data were analyzed using AMOS Version 26 software via Structural Equation Modeling (SEM). Findings indicate that while teachers' attitudes towards SD reported the highest mean score (M = 5.51, SD = 0.719), followed closely by their knowledge of SD (M = 5.49, SD = 0.784), these factors did not directly influence their pedagogical approaches to SD. However, the study revealed significant direct effects of attitudes towards SD (β = .251, p < .001), knowledge about SD (β = .223, p < .001), and school support (β = .272, p < .001) on ESD teaching self-efficacy. Furthermore, ESD teaching self-efficacy exhibited a significant and positive direct effect on pedagogical approaches (β = .387, p < .001), underscoring the critical role of teacher confidence in implementing SD-focused STEM education. Additionally, school support also demonstrated a positive direct effect on pedagogical approaches (β = .111, p = .014), highlighting the importance of institutional backing in promoting effective SD pedagogy. The results suggest that enhancing teachers' self-efficacy through positive attitudes, robust knowledge, and strong school support are key strategies for fostering effective SD-oriented STEM education in line with the SDGs.